DAMPAK LINGKUNGAN KELUARGA TERHADAP MINAT MAHASISWA PENDIDIKAN EKONOMI UNIVERSITAS NEGERI SURABAYA UNTUK MENJADI GURU - Mevia Dwi Cahya P.H (FKIP Unswagati, 2025)
The purpose of this study is to ascertain how the family environment affects the interest of State University of Surabaya Economics Education students in pursuing a career as a teacher or teaching staff member. This study uses a quantitative method, using a purposive sampling technique using an ex-post facto approach. For the respondents, this study involved students who have an economic education background and are undergoing studies at the State University of Surabaya class of 2022, 2023, and 2024 with a minimum sample of 115 respondents. Data collection was carried out by distributing questionnaires or questionnaires on the Likert scale, with a score of 1 to 5. Validity and rehabilitation tests were carried out before data analysis. Analysis methods include descriptive and inductive analysis, including normality tests, multi-collinearity, heteroskedanity, and simple linear regression. Keywords: Family background, Interest in becoming a teacher, Career.